Assistance for Soy Milk SMEs in Sidoarjo to Increase Production and Sales Post-Covid-19 Pandemic - Iswanto; Jakaria, Ribangun B.; Rahmawati, Yunianita (Procedia of Social Sciences and Humanities, 2022)
Sumber Rejeki is a producer of soy milk drinks located in Sumorame Village, Sidoarjo Regency with the Seven soy brand. In line with its growing business, UD. Sumber Rejeki tries to make several innovations to increase its production and sales. However, the efforts made could not be maximized due to several things, including: production equipment and facilities owned were still limited, there was no scheduling and production planning, the soy milk produced could not last long, the market and distribution were still limited, the media used to market the product is still limited. So with some of the problems faced, several solutions were taken to overcome these problems, namely: first by providing a production tool in the form of a bottle cap machine, the hope is that production will increase. Second, by designing the distribution system and online marketing.